Ultrasonic Sensor-Based Automated Water Dam Shutter - Kommey, Benjamin; Kotey, Seth Djanie; Opoku, Daniel (Universitas Andalas, 2020)
Monitoring the level of water in dams is necessary to ensure optimal operation and safety. Water level monitoring is normally done manually by a full-time operator. This results mostly in a waste of water due to the inability of the operator to accurately determine the quantity of water to release from the dam gate. The aim of this paper is to present the design of a system to automatically open and close dam gates based on the level of water in the dam. The system is based on a low-cost microcontroller and an ultrasonic sensor to read water level in the dam. SMS messages are sent to nearby residents to warn them of the opening of the dam gate. An alarm is also sounds before the eventual opening of the dam gate.